Optimalisasi Daya Saing Biji Kakao Indonesia di Pasar Malaysia Berbasis Pemberdayaan Masyarakat - Siti Widiati; Alfarid Fajar; Ayu Nida Afifah; Mikhael Beni Dito (AGRIBIOS, 2026)
Indonesia is one of the largest cocoa producers in the world with great potential in the agribusiness sector, but the quality of cocoa still faces challenges in meeting international standards. This study aims to analyze the competitiveness of Indonesian cocoa in the Malaysian market using the Revealed Comparative Advantage (RCA) method and identify strategies to improve quality and diversify products. The results showed that the average RCA value of Indonesian cocoa was 3.2 which indicated strong competitiveness, although it fluctuated with the highest value in 2013 (8.0) and the lowest in 2021 (0.9). To increase competitiveness, a strategy of product diversification is needed through processing cocoa into value-added products and the application of fermentation technology to improve the quality of cocoa beans. In addition, the empowerment of farmers through technical training and expanded access to technology is an important factor in strengthening Indonesia's cocoa position in the international market. Trade policy adjustments, such as the evaluation of progressive tariffs and the provision of incentives for the local processing industry, are also needed to support the sustainability of the cocoa sector. This research shows that product diversification and good post-harvest management play a role in increasing community empowerment and comparative advantage in the global market.